IMPACT OF MERGER OF DENA BANK AND VIJAYA BANK ON SHARE PRICE OF BANK OF BARODA: AN EVENT STUDY (International Journal of Food and Nutritional Sciences, 2022)
The objective of the paper is to investigate stock market responses to merger announcement and its impact on share price of merged banks in short term. The study involves sample of Bank of Baroda, Dena Bank and Vijaya Bank which merged on 1 April 2019 by employing Event Study methodology. The data has been collected from CMIE data base and Yahoo finance database. The study utilizes CAR and BHAR calculated on basis of Market Adjusted Model and T statistics to know the significance. It reveals that in banking environment marked by frequent merger, such transaction directly/indirectly affect the shareholders sentiments and increase the market shares i.e merger enhances the performance and wealth for both businesses and shareholders. Based on the statistical results the conclusion drawn is that merger announcement has no impact on the shareholders value of Bank of Baroda.